Family occurrence of schistosomal hepatosplenomegaly and maternal effect - Tavares-neto, José [UNESP]; Prata, Aluizio [UNESP] (Sociedade Brasileira de Medicina Tropical - SBMT, 1989)
In this paper we present a study of members of 265 nuclear families, aged six or more. This study is based of family heredograms, and takes into account the clinical form ofschistosomiasis observed before treatment with oxamniquine. The probability of occurrence of two or more cases ofhepatosplenomegaly is low, notwithstanding the fact that it was observed in 38 families. Even less frequent is the occurrence of three or more cases observed in 17 families (P=0.002). The concentration of the hepatosplenic form was higher among siblings than it was among mothers and children, or fathers and children. It was found to be not significant between husband (father) and wife (mother). These observations reinforce the evidence for the presence of a genetic component in susceptibility to the hepatosplenic form of the disease. In cases in which the mother was hepatosplenic there was a higher incidence of hepatosplenic children; the relative risk was a least five times higher than in those in which the father was the affected member (the maternal effect). In cases where both members were affected by the hepatointestinal form, the risk to the filial generation was similar to that of the population in general. Thus, in the process towards severe forms of Schistosomiasis mansoni, pre and post natal factors might be involved.

As formas clínicas da esquistossomose mansônica, anteriores ao tratamento com oxamniquine, foram estudadas nos membros de 265famílias, com seis anos ou mais de idade. A probabilidade da ocorrência de dois ou mais casos, na mesma família, da hepatosplenomegalia esquistossomótica (HE) é baixa, no entanto foi observada em 38 famílias; menor probabilidade (P = 0,002) devia ocorrer três ou mais casos, porém dezessete famílias estavam nesta situação. A concentração da forma HE foi alta entre irmãos, comparativamente à observada entre mães e filhos epais e filhos. Não sendo significante a concentração encontrada no casal entre marido e mulher. Estas observações reforçam a evidência do efeito do componente genético da' susceptibilidade para a forma HE. Também, quando a mãe era hepatosplênica (HE) a prevalência desta forma nos filhos foi maior; o risco relativo foi cinco vezes superior (efeito materno), comparado ao encontrado quando era o pai hepatosplênico. Quando ambos os genitores eram hepatointestinal os riscos relativos da forma HE, nos filhos, foi semelhante ao da população geral. Assim, provavelmente fatores pré e pós- natais também estarão envolvidos na predisposição da forma hepatosplênica.
Keywords: Schistosomiasis; Family occurrence; Maternal effect; Esquistossomose; Recorrência familial; Efeito materno